Incidence and cost of medication harm in older adults following hospital discharge: a multicentre prospective study in the UK - Parekh, Nikesh; Ali, Khalid; Stevenson, Jennifer M.; Davies, J. Graham; Schiff, Rebekah; Van der Cammen, Tischa; Harchowal, Jatinder; Raftery, James; Rajkumar, Chakravarthi (British journal of clinical pharmacology, 2018)
Aims Polypharmacy is increasingly common in older adults, placing them at risk of medication‐related harm (MRH). Patients are particularly vulnerable to problems with their medications in the period following hospital discharge due to medication changes and poor information transfer between hospital and primary care. The aim of the present study was to investigate the incidence, severity, preventability and cost of MRH in older adults in England postdischarge. Methods An observational, multicentre, prospective cohort study recruited 1280 older adults (median age 82 years) from five teaching hospitals in Southern England, UK. Participants were followed up for 8 weeks by senior pharmacists, using three data sources (hospital readmission review, participant telephone interview and primary care records), to identify MRH and associated health service utilization. Results Overall, 413 participants (37%) experienced MRH (556 MRH events per 1000 discharges), of which 336 (81%) cases were serious and 214 (52%) potentially preventable. Four participants experienced fatal MRH. The most common MRH events were gastrointestinal (n = 158, 25%) or neurological (n = 111, 18%). The medicine classes associated with the highest risk of MRH were opiates, antibiotics and benzodiazepines. A total of 328 (79%) participants with MRH sought healthcare over the 8‐week follow‐up. The incidence of MRH‐associated hospital readmission was 78 per 1000 discharges. Postdischarge MRH in older adults is estimated to cost the National Health Service £396 million annually, of which £243 million is potentially preventable. Conclusions MRH is common in older adults following hospital discharge, and results in substantial use of healthcare resources.